You are on page 1of 4

www.urdulovers123.blogspot.

com

Punjab College
Khanewal Exercise 2.8 (Solutions)
Taylor Series Expansion of Function
h2 h3
f ( x + h) = f ( x) + hf ( x ) + f ( x) + f ( x ) + ....
2! 3!
Maclaurin Series
x2 x3
f ( x ) = f (0) + xf (0) +
f (0) + f (0) + ....
2! 3!

Question # 1(i)
Let f ( x ) = ln(1 + x) f (0) = ln(1 + 0) = 0
d 1 1
f ( x ) = ln(1 + x) = f (0) = = 1
dx 1+ x 1+ 0
d
(1 + x ) = - (1 + x ) f (0) = - (1 + 0 ) = - 1
-1 -2 -2
f ( x ) =
dx
d
f ( x) = -(1 + x) -2 = + 2(1 + x) -3 f (0) = 2(1 + 0) -3 = 2
dx
d
2 (1 + x ) = - 6 (1 + x ) f (iv ) (0) = - 6 (1 + 0 ) = - 6
-3 -4 -4
f ( iv ) ( x) =
dx
By Maclaurin series
x2 x3
f ( x ) = f (0) + xf (0) + f (0) + f (0) + ......
2! 3!
x2 x3 x4
ln(1 + x ) = 0 + x(1) + (-1) + (2) + (-6) + ......
2! 3! 4!
2 3 4
x x x
= x- + (2) - (6) + ......
2 1 3 2 1 4 3 2 1
x 2 x3 x4
= x - + - + ......
2 3 4

Question # 1(ii)
Let f ( x ) = cos x f (0) = cos(0) = 1
d
f ( x ) = cos x = - sin x f (0) = - sin(0) = 0
dx
d
f ( x) = ( - sin x ) = - cos x f (0) = - cos(0) = - 1
dx
d
f ( x) = ( - cos x ) = + sin x f (0) = sin(0) = 0
dx
d
f ( iv ) ( x) = sin x = cos x f (iv ) ( x ) = cos(0) = 1
dx
d
f ( v ) ( x) = cos x = - sin x f (v ) ( x) = - sin(0) = 0
dx
d
f ( vi ) (0) = ( - sin x ) = - cos x f ( vi ) ( 0 ) = - cos(0) = - 1
dx
Now by Maclaurin series
x2 x3
f ( x ) = f (0) + xf (0) + f (0) + f (0) + ......
2! 3!

Math, Physics, Chemistry And Other Study Notes Freely Available Below Link
FSc-II / Ex- 2.8 - 2 www.urdulovers123.blogspot.com

x2 x3 x4 x5 x6
cos x = 1 + x(0) + (-1) + (0) + (1) + (0) + (-1) + ......
2! 3! 4! 5! 6!
2 4 6
x x x
= 1+ 0 - + 0 + + 0 - + ......
2! 4! 6!
2 4 6
x x x
= 1 - + - + ......
2! 4! 6!

Question # 1(iii)
Let f ( x ) = 1 + x
1
= (1 + x ) 2
1
f (0) = (1 + 0) 2 = 1
d 1 1 -1 1 -1
f ( x) = (1 + x ) 2 = (1 + x ) 2 (1) = (1 + x ) 2
dx 2 2
1 1 1
f ( 0 ) = (1 + 0 ) 2 =
-

2 2
d 1 - 1
f ( x ) = ( )
-3
2 = - (1 + x ) 2
1
1 + x
dx 2 4
1 -3 1
f (0) = - (1 + 0 ) 2 = -
4 4
1 d 1 3 -5
1 + x ) 2 = - - (1 + x ) 2 = (1 + x ) 2
3 3 -5
(
-
f ( x) = -
4 dx 4 2 8
3 -5 3
f ( 0 ) = (1 + 0 ) 2 =
8 8
Now by Maclaurin series
x2 x3
f ( x ) = f (0) + xf (0) + f (0) + f (0) + ......
2! 3!
1 x 2 1 x3 3
1 + x = 1 + x + - + + .....
2 2! 4 3! 8
1 x 2 1 x3 3
= 1 + x + - + + .....
2 2 4 6 8
x x 2 x3
= 1 + - + + .....
2 8 16

Question # 1(iv)
Let f ( x ) = e x f (0) = e 0 = 1

f ( x ) = ( )
d x
dx
e = e x f ( 0 ) = e0 = 1

f ( x ) = ( )
d x
dx
e = e x f ( 0 ) = e0 = 1

f ( x ) = ( )
d x
dx
e = e x f ( 0 ) = e0 = 1
By Maclaurin series
x2 x3
f ( x ) = f (0) + xf (0) + f (0) + f (0) + ......
2! 3!
x2 x3
e = 1 + x (1) + (1) + (1) + .....
x
2! 3!
2 3
x x
= 1 + x + + + .....
2! 3!

Math, Physics, Chemistry And Other Study Notes Freely Available Below Link
www.urdulovers123.blogspot.com FSc-II / Ex- 2.8 - 3

Questoion # 1(v)
Let f ( x ) = e 2 x f (0) = e2(0) = e0 = 1
f ( x ) =
d 2x
dx
e( ) = 2e 2 x f ( 0 ) = 2e 2(0) = 2(1) = 2

f ( x ) = 2
d 2x
dx
e( ) ( )
= 2 2e2 x = 4e 2 x f ( 0 ) = 4e 2(0) = 4(1) = 4

f ( x ) = 4
d 2x
dx
e( ) ( )
= 4 2e 2 x = 8e2 x f ( 0 ) = 8 e2(0) = 8
By Maclaurin series
x2 x3
f ( x ) = f (0) + xf (0) + f (0) + f (0) + ......
2! 3!
x2 x3
e 2 x = 1 + x (2) + (4) + (8) + .....
2! 3!
2 3
4x 8x
= 1 + 2x + + + .....
2! 3!

Question # 2
Let f ( x ) = cos x
d
f ( x ) = cos x = - sin x
dx
d
f ( x ) = - sin x = - cos x
dx
d
f ( x ) = - cos x = - ( - sin x ) = sin x
dx
By Taylor series
h2 h3

f ( x + h) = f ( x) + hf ( x ) +
f ( x) + f ( x ) + ....
2! 3!
h2 h3
cos ( x + h ) = cos x + h ( - sin x ) + ( - cos x ) + ( sin x ) + ......
2! 3!
2 3
h h
cos ( x + h ) = cos x - h sin x - cos x + sin x + ......
2 3
p
Put x = 60o and h = 1o = = 0.01745 rad
180
( 0.01745 ) ( 0.01745 )
2 3

cos ( 60 + 1) = cos60 - ( 0.01745 ) sin 60 - cos60 + sin 60 + ......


2 3

cos61o = 0.5 - ( 0.01745 )( 0.866 ) -


( 0.000305) 0.5 + ( 0.00000531) 0.866 + ......
( ) ( )
2 6
= 0.5 - 0.0151117 - 0.000076125 + 0.000000072 + ......
= 0.484812247 0.4848

Question # 3
Let f ( x) = 2 x
d x d x
f ( x ) = 2 Q a = a x ln a
dx dx
= 2 ln 2
x

d
( )
f ( x ) = ln 2 2 x = ln 2 2 x ln 2 = ( ln 2 ) 2 x
dx
2

2 d
f ( x ) = ( ln 2 ) 2 x = ( ln 2 ) 2 x ln 2 = ( ln 2 ) 2 x
2 3

dx

Math, Physics, Chemistry And Other Study Notes Freely Available Below Link
FSc-II / Ex- 2.8 - 4 www.urdulovers123.blogspot.com

Now by Taylor series


h2 h3
f ( x + h) = f ( x) + hf ( x ) + f ( x) + f ( x ) + ....
2! 3!
h2 h3
2 x+ h = 2 x + h 2 x ln 2 + ( ln 2 ) 2 x + ( ln 2 ) 2 x + ......
2 3

2! 3!
2 h
2
3 h
3

= 2 x 1 + ( ln 2 ) h + ( ln 2 ) + ( ln 2 ) + ......
2! 3!

Question # 2(Old Book)


Let f ( x) = sin x and h = y
d
f ( x) = sin x = cos x
dx
d
f ( x ) = cos x = - sin x
dx
d
f ( x ) = - sin x = - cos x
dx
d
f ( iv ) ( x ) = - cos x = - ( - sin x ) = sin x
dx
d
f ( v ) ( x) = sin x = cos x
dx
Now by Taylor series
h2 h3
f ( x + h) = f ( x) + hf ( x ) + f ( x) + f ( x ) + ....
2! 3!
y2 y3 y4 y5
sin( x + y ) = sin x + y (cos x) + (- sin x ) + (- cos x) + (sin x) + (cos x ) + .....
2! 3! 4! 5!
y 2
y 4
y 3
y 5

= sin x 1 - + - .... + cos x y - + - ....
2! 4! 3! 5!
y 2 y4 y 3 y5
Since cos y = 1 - + - .... and sin y = y - + - ....
2! 4! 3! 5!
Therefore
sin( x + y ) = sin x cos y + cos x sin y

Question # 3(Old Book)

Math, Physics, Chemistry And Other Study Notes Freely Available Below Link